Análisis e Interpretación a los Estados Financieros de la Ferretería “Ferri eléctrico Industrial” del Cantón Catamayo, periodos 2021- 2022 - Cabrera Armijos, María Iliana (2024)
This Curricular Integration Work was developed with the objective of performing the Financial Analysis of the Hardware Store “Ferri eléctrico Industrial” during the years 2021-2022, with the purpose of knowing the economic and financial situation of the hardware store in the referred years. In the course of the development of the work, the proposed objectives were met, through the application of vertical and horizontal analysis to know the variation of each of the accounts involved, another objective was the determination of financial indicators to verify the working capital, liquidity, indebtedness, activity and profitability. For the development of the vertical and horizontal analysis, Excel spreadsheets have been used, which facilitates the calculations and their respective representations with statistical graphs, in an efficient and precise manner, thus becoming an effective and versatile tool for data processing and analysis. The methodology used had a mixed approach involving qualitative and quantitative information, in a deductive, descriptive and exploratory research environment. As a result, it was found that the hardware store has not carried out any financial analysis since its creation, so the owner could not know the real economic situation of the company. In this context, after applying the financial analysis both vertically and horizontally, the financial structure of the hardware store “Ferri eléctrico Industrial” was determined for the period 2021 - 2022. It was determined that current assets were very significant, with inventories being the account with the highest concentration, due to the fact that there is an excess of merchandise.